2016
DOI: 10.1021/acs.iecr.6b02657
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation Rate of 2-Amino-2-methyl-1-propanol to Cyclic 4,4-Dimethyl-1,3-oxazolidin-2-one: Experiments and Kinetics Modeling

Abstract: Employing experimental kinetics data collected in this study, a power law rate equation for the thermal degradation of 2-amino-2-methyl-1-propanol (AMP) to 4,4-dimethyl-1,3-oxazolidin-2-one (DMOZD) as a function of amine and CO 2 concentration in the solution is introduced. The rate experiments were carried out at 120, 135, and 150 °C. Kinetic data was collected to extract the initial rate equation from aqueous solutions of 1.12, 1.68, 2.24, and 3.36 M, AMP and CO 2 loadings from 0.17 to 0.7, mol CO2 / mol AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…7 The strong hydrogen bonding interaction between nitrogen of AMP and an adjacent water molecule tends to suppress the direct reaction of CO 2 with AMP leading to carbamate formation while facilitating the bicarbonate reaction route. 8,9 According to recent experimental studies, 10,11 AMP may undergo thermal degradation at high stripping temperatures while its main degradation product is found to be 4,4-dimethyl-1,3-oxazolidin-2-one (DMOZD). To explain the DMOZD formation, it has been suggested that AMP could form carbamate (AMPCOO − ) by reacting with CO 2 , 12 similar to the case of MEA.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The strong hydrogen bonding interaction between nitrogen of AMP and an adjacent water molecule tends to suppress the direct reaction of CO 2 with AMP leading to carbamate formation while facilitating the bicarbonate reaction route. 8,9 According to recent experimental studies, 10,11 AMP may undergo thermal degradation at high stripping temperatures while its main degradation product is found to be 4,4-dimethyl-1,3-oxazolidin-2-one (DMOZD). To explain the DMOZD formation, it has been suggested that AMP could form carbamate (AMPCOO − ) by reacting with CO 2 , 12 similar to the case of MEA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…From previous experiments, it is now well known that bicarbonate is the predominant product of CO 2 capture by aqueous AMP under absorber conditions. , In addition, recent first-principles studies have revealed that bicarbonate formation via amine-catalyzed hydrolysis can be kinetically more favorable than carbamate formation at relatively low absorber temperatures (<330 K) . The strong hydrogen bonding interaction between nitrogen of AMP and an adjacent water molecule tends to suppress the direct reaction of CO 2 with AMP leading to carbamate formation while facilitating the bicarbonate reaction route. , According to recent experimental studies, , AMP may undergo thermal degradation at high stripping temperatures while its main degradation product is found to be 4,4-dimethyl-1,3-oxazolidin-2-one (DMOZD). To explain the DMOZD formation, it has been suggested that AMP could form carbamate (AMPCOO – ) by reacting with CO 2 , similar to the case of MEA.…”
Section: Introductionmentioning
confidence: 99%
“…The initial bulk 2amino-2-methyl-1-propanol (AMP; Acros Organics) and 1amino-2-propanol (A2P; Sigma-Aldrich) solutions were prepared to the target carbon dioxide content. 32 Table 1 shows the composition of each amine in the solutions, along with the total CO 2 loading. The solvent test matrix is composed of seven different combinations of AMP and A2P at CO 2 -rich loading conditions, along with four equal composition blends at four different CO 2 -loadings from lean to rich.…”
Section: Methodsmentioning
confidence: 99%
“…31 AMP can be prone to degradation at high temperatures, despite its perception as generally being resistant to degradation. 32,33 Previous studies have shown that AMP can form a carbamate (AMPCOO − ) with CO 2 leading to thermal degradation with a similar pathway to that of MEA. 32,34−36 The thermal degradation rate of AMP to its main degradation product, 4,4-dimethyl-1,3-oxazolidin-2-one (DMOZD), was investigated in detail by considering an apparent reaction rate and pseudo-mechanistic approach.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 In the present work, a novel solid−liquid nonaqueous solution is proposed for CO 2 capture, which will not only feature the advantage of the nonaqueous solution but also that of biphasic solvent and is expected to alleviate the above shortcomings. Combined with the favorable regeneration performance of AMP 35,36 and fast reaction rate of PZ, 21,37 the amine blend of AMP and PZ ensures excellent performance on CO 2 capture. The organic solvent dipropylene glycol dimethyl ether (DME) with a high boiling point and low viscosity is serviced as the solvent and phase splitter, which is considering as an environmentally friendly solvent for nonhazardous in the list of air pollution by the United States and the European Union.…”
Section: ■ Introductionmentioning
confidence: 99%